2021
DOI: 10.18632/aging.203377
|View full text |Cite
|
Sign up to set email alerts
|

RNA N6-methyladenosine demethylase FTO promotes osteoporosis through demethylating Runx2 mRNA and inhibiting osteogenic differentiation

Abstract: As a systemic disease, osteoporosis (OP) results in bone density loss and fracture risk, particularly in the hip and vertebrae. However, the underlying molecular mechanisms of OP development have not been fully illustrated. N6-Methyladenosine (m6A) is the most abundant modification of mRNAs, which is involved in many of pathological processes in aging disease. However, its role and regulatory mechanism in OP remains unknown. Here, we aimed to investigate the roles of m6A and its demethylase FTO in OP developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 21 publications
2
37
0
Order By: Relevance
“…Xie et al revealed that TNF-α induced m6A modification in ELMO1 3′UTR triggers directional migration of mesenchymal stem cell in ankylosing spondylitis patients [ 30 ]. Wang et al elucidated a new pathogenesis of osteoporosis, that is, FTO mediates Runx2 mRNA demethylation to inhibit the osteogenic differentiation of BMSCs [ 31 ]. However, the roles of m6A modification and the underlying regulatory mechanisms in SONFH remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al revealed that TNF-α induced m6A modification in ELMO1 3′UTR triggers directional migration of mesenchymal stem cell in ankylosing spondylitis patients [ 30 ]. Wang et al elucidated a new pathogenesis of osteoporosis, that is, FTO mediates Runx2 mRNA demethylation to inhibit the osteogenic differentiation of BMSCs [ 31 ]. However, the roles of m6A modification and the underlying regulatory mechanisms in SONFH remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…We found FTO upregulated in OP, whereas YTHDF2 and CBLL1 were downregulated in OP. Previous studies have indicated that FTO inhibits osteogenic differentiation to promote OP ( 26 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is a bone aging disease. m 6 A modification have been reported to be involved in regulating the proliferation, differentiation, and apoptosis of bone-related cells including bone marrow mesenchymal stem cells, osteoblasts, and osteoclasts by multiple studies ( Huang et al, 2021 ) ( Wang et al, 2021b ; Chen et al, 2022 ) ( Wu et al, 2020 ). In addition, IGF2BP2 highly expressed in Alzheimer’s patients by bioinformatic analysis using multiple RNA-seq datasets of Alzheimer’s brain tissues ( Deng et al, 2021 ).…”
Section: M 6 a Methylation Modification In Female ...mentioning
confidence: 99%